The Effect Of Perineal Massage On The Insidence Perineal Rupture In Labour In Nene Mallomo Hospital Sidenreng Rappang - Jamir, A. Fatimah; Tajuddin, Titin (Akademi Kebidanan Bunga Husada Samarinda, 2021)
Background: one of the causes of direct maternal death related to childbirth is bleeding (28%). Perineal rupture is the most common cause of post partum hemorrhage after uterine atony. One way to reduce perineal rupture is to do perineal massage to train and stretch the perineal tissue to make it more soft and elastic. Objective: to determine the effect of perineal massage on the incidence of perineal rupture in labor. Methods: This study was a quasi-experimental design with an